PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT. RAHAYU SUMBER ELECTRIC CISOKA KABUPATEN TANGERANG - Niken Indriyani; Laura Komala (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of the Physical Work Environment on Employee Performance, the effect of Communication on Employee Performance, and to determine the effect of the Physical Work Environment and Communication simultaneously on Employee Performance at PT. Funworld Prima, Ciputra Mall Branch, West Jakarta. The research method used is a quantitative method, with data collection techniques through distributing questionnaires to the entire population of 54 people with saturated sampling techniques. Data analysis techniques used in this study include validity tests, reliability tests, classical assumption tests, linear regression analysis, correlation coefficient tests, determination coefficients, and hypothesis testing using t tests (partial) and F tests (simultaneous). The results showed that the physical work environment (X1) had a positive and significant effect on employee performance (Y). This was proven by a simple linear regression test (Y = 30.214 + 0.183X1) and a t test on the physical work environment variable (X1) obtained a significance value of 0.001 <0.005 and a calculated t value of 3.382 > t table 1.676. Communication has a more dominant influence than the work environment on employee performance. Communication (X2) has a positive and significant effect on employee performance (Y). This is evidenced by a simple linear regression test (Y = 29.612 + 0.199X2) and a t-test on the communication variable (X1), which obtained a significance value of 0.000 <0.005 and a calculated t-value of 4.014 > t-table 1.676. (Y = 26.033 + 0.140X1 + 0.163X2) and an F-test on the physical work environment (X1) and communication (X2) variables simultaneously, obtained a significance value of 0.000 <0.005 and a calculated F-value of 18.616 > 3.11 (F-count > F-table). This means that the Physical Work Environment and Communication variables jointly have a significant effect on Employee Performance at PT. Funworld Prima, Ciputra Mall Branch, West Jakarta.